Shaping Ability of Single-File Systems with Different Movements: A Micro-Computed Tomographic Study - Santa-Rosa, Joedy; Damião de Sousa-Neto, Manoel; Versiani, Marco Aurelio; Nevares, Giselle; Xavier, Felipe; Romeiro, Kaline; Cassimiro, Marcely; Bianchi Leoni, Graziela; Ferraz de Menezes, Rebeca; Albuquerque, Diana (Iranian Endodontic Journal, 2016)
Introduction: This study aimed to perform a rigorous sample standardization and also evaluate the preparation of mesiobuccal (MB) root canals of maxillary molars with severe curvatures using two single-file engine-driven systems (WaveOne with reciprocating motion and OneShape with rotary movement), using micro-computed tomography (micro-CT). Methods and Materials: Ten MB roots with single canals were included, uniformly distributed into two groups (n=5). The samples were prepared with a WaveOne or OneShape files. The shaping ability and amount of canal transportation were assessed by a comparison of the pre- and post-instrumentation micro-CT scans. The Kolmogorov-Smirnov and t-tests were used for statistical analysis. The level of significance was set at 0.05. Results: Instrumentation of canals increased their surface area and volume. Canal transportation occurred in coronal, middle and apical thirds and no statistical difference was observed between the two systems (P>0.05). In apical third, significant differences were found between groups in canal roundness (in 3 mm level) and perimeter (in 3 and 4 mm levels) (P<0.05). Conclusion: The WaveOne and One Shape single-file systems were able to shape curved root canals, producing minor changes in the canal curvature. Keywords: Micro-Computed Tomography; OneShape; Reciprocating Motion; Rotary System; WaveOne